2022
DOI: 10.14710/kapal.v19i3.48319
|View full text |Cite
|
Sign up to set email alerts
|

CFD Simulation Verification Processes at Planing Hulls using An Interceptor

Abstract: Experimental test is one of the methods for predicting drag ships using towing tank. This method has a good level of accuracy but requires quite complex equipment and costs. With the advancing technology of computing, the CFD method has emerged as an alternative for problem-solving, especially in hydrodynamics analysis. This study aims to ensure the accuracy of Computational Fluid dynamics (CFD) by verifying experimental data on high-speed vessel using an interceptor. The Interceptor system generates a hydrody… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 14 publications
0
1
0
Order By: Relevance
“…Some differences were also identified in the calculation errors due to difficulties in modeling an object in numerical computation based on the conditions used in experimenting with towing tanks. A similar trend has been reported by Hosseini et al [34] and Utomo et al [21] during the application of CFD calculations to planing ships, presenting an error of 4.63% to 9.97% in predicting ship resistance compared to the experimental results.…”
Section: Model Validationsupporting
confidence: 85%
See 1 more Smart Citation
“…Some differences were also identified in the calculation errors due to difficulties in modeling an object in numerical computation based on the conditions used in experimenting with towing tanks. A similar trend has been reported by Hosseini et al [34] and Utomo et al [21] during the application of CFD calculations to planing ships, presenting an error of 4.63% to 9.97% in predicting ship resistance compared to the experimental results.…”
Section: Model Validationsupporting
confidence: 85%
“…Several other experiments were conducted on high-speed vessels to measure resistance, trim, and center of gravity values at different interceptor speeds and heights. The results showed that the pressure under the transom increased in proportion to the size of the interceptor [20], [21]. Furthermore, Samuel et al studied the integration of the appendage in the Aragon 2 hull design and reported a 57% drag reduction in the close-to-chine position [22].…”
Section: Introductionmentioning
confidence: 99%
“…The results showed that the numerical method has the same phenomenon as the experiment: the ship has self-righting in all condition load cases. Numerical methods such as CFD have become famous for marine use, such as fast ship design [3,4] and ship performance [5,6]. Another CFD scheme such as mesh-free CFD, i.e., smoothed particle hydrodynamics (SPH) that is suitable for marine engineering cases such as water wave propagation [7,8] and sloshing in LNG cases [9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…To prevent this, the vessel can be equipped with devices that actively or proactively control the trim angle, or modifications can be made to the hull. Applying a trim control device on a high-speed craft, such as such as interceptor [49][50][51][52][53][54][55][56][57][58], trim tab [59][60][61], the combination of interceptor and trim tab [50,58] [41,45], and stern foil [62][63][64][65][66], can reduce drag and trim angle. Modifying the hull shape can also reduce the boat's drag, thus improving its performance, such as with a step hull [67] and tunneled hull [68], as examples.…”
Section: Introductionmentioning
confidence: 99%